Synthesis and property of EPEG‐based polycarboxylate ether superplasticizers via RAFT polymerization. Issue 9 (23rd June 2022) - Chen, Xiaodong; Tang, Xinde; Zhang, Cuizhen; Lu, Xiao; Guo, Haichao; Li, Xuefan; Pang, Laixue; Yang, Yong; Dong, Fuying
Abstract: Polycarboxylate ether superplasticizers (PCEs) with comb‐shaped molecular structures have attracted considerable attention in the area of admixtures for construction engineering. However, there are some contradictions in studying the relationship between the molecular structure and property of PCE due to its random structure based on traditional free radical polymerization, which is confused for designing and developing novel PCEs. In this article, a series of reversible addition fragmentation chain transfer (RAFT) polymerization‐based polycarboxylate ether superplasticizers (RPCs) were prepared by the copolymerization of acrylic acid (AA) and ethylene‐glycol monovinyl polyethylene glycol (EPEG). The chemical structure and composition of RPCs were characterized and their adsorption behavior and dispersion properties were conducted. The results demonstrate that the molecular weights of RPCs do not vary significantly with prolonging reaction time, and the actual monomer ratio in RPCs displays a significant change to the feed one due to the monomer reactivity and conversion at higher reaction temperature, which is different from conventional free radical polymerization. The dispersion and adsorption properties of RPCs to cement were evaluated by slurry fluidity tests and total organic carbon (TOC) experiments. The effect of polymerization temperature and time on the dispersion ability has been systematically studied. The results indicate that the dispersion ability and adsorption capacity of RPCs are closely related to their molecular structures. The dispersion ability of RPCs were enhanced with increasing carboxyl group density in a certain range of monomer molar ratios (≤6:1). This study will provide a new platform for designing and developing high‐performance and rational cost‐effective superplasticizers with well‐defined structure and controlled molecular weight. Abstract : Polycarboxylate superplasticizers were synthesized via RAFT polymerization, and their dispersion ability and adsorption capacity to cement are closely realated to the molecular structures.